Handbook of cardiac electrophysiology - Natale, Andrea; Wazni, Oussama (Informa Healthcare, 2007)
The first practical, user-friendly guide to the theory and practice of a routinely used technique, this new manual provides the specialist in training with a thorough grounding in the equipment, procedures, and clinical findings with which clinicians need to be familiar. Conceived as an alternative to the large and expensive texts aimed at specialists, the handbook is divided into two sections, which present: -- a review of the main kinds of arrhythmia, with illustrations of typical ECG findings supported where appropriate by correlative imaging -- the principal diagnostic and therapeutic procedures, including implantation of pacemakers, resynchronization therapy, use and placement of catheters and ablation techniques Providing practical guidance on clinical applications, and illustrated with numerous graphics, checklists and flowcharts to enable readers to locate information quickly and easily, Handbook of Cardiac Electrophysiology is an accessible resource covering a widespread, but complex technology.